MOTIVATION AND IMPLEMENTATION OF EMPLOYEES PERFORMANCE OF NUGRAHA EKAKURIR TRACK, LTD IN SURAKARTA - Ipung Sri Purwanti Hery; Hartati Dyah Wahyuningsih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Exemplary leaders motivate employees in building company performance. The study shows that motivation has an important influence on employee performance. The purpose of this study was to determine whether motivation had an effect on employee performance at Nugraha EkakurirTrack, Ltd in Surakarta. Hasibuhan's theory (2010) and Robbins (2011) state that performance is the result of work achieved based on motivation. This study uses a quantitative approach. Sample 70 employees of Nugraha Ekakurir, Ltd Surakarta route was taken by census with a saturated sampling technique. Questionnaire as an instrument to collect data. The data obtained were analysed by linear regression test, t test, and R^2 test. Regression test shows that motivation has a significant positive effect on the performance of Nugraha Ekakurir Track, Ltd in Surakarta. In relation to the t test, it shows that the motivation variable has a significant effect on the performance of employees of Nugraha Ekakurir Track, Ltd in Surakarta. Meanwhile, the results of the R2 test obtained the number 0.656 or 65.6% of employee performance is influenced by motivation, the remaining 34.4% is influenced by variables outside the study. The results of this study are useful as guidelines and recommendations and references for management practitioners, and researchers, especially those related to Human Resource research. Keywords: Motivation, Employee Performance.